Characteristics and Endoscopy Findings of Liver Cirrhosis Patients at Waled Hospital, Cirebon, Indonesia (2020-2023) - Azahra, Afifah Humaira; Sedayu, Sedayu; Zein, Ahmad Fariz Malvi Zamzam (GHMJ (Global Health Management Journal), 2024)
Background: Hepatic cirrhosis is a terminal manifestation of chronic liver disease. The causes of cirrhosis in the Asia Pacific it was caused by hepatitis B. Older adults are more likely to experience complications, which might be due to abnormalities in the liver. Various complications occurred during the progression from compensated to decompensated, and endoscopic examination showed images of gastroesophageal varices or PHG. Aims: The aim was to determine the characteristics of liver cirrhosis patients and the endoscopy findings at waled hospital from 2020 to 2023. Methods: This research used descriptive observational methods. The sample in this study were patients with liver cirrhosis at Waled hospital from 2020-2023, there were 135 sample who were selected using total sampling techniques. Information was acquired from medical records of 33 patients who met the consideration rules. Results: This study showed that the largest number of patients with liver cirrhosis based on age 45 years old (12.1%), predominantly male (72.7%), with the etiology hepatitis B (69.7%), and all (100%) were in decompensated stage. Endoscopy results revealed that the majority of patients experiences esophageal varices and PHG (54.5%), with grade 3 esophageal varices (81.8%) and mild grade PHG (60.6%) dominating. Conclusion: The majority of patients with liver cirrhosis were 45 years old, predominantly male, with the most common etiology hepatitis B, and all were in the decompensated stage. The most common endoscopy results showed esophageal varices and PHG, with grade 3 esophageal varices and mild grade PHG. Received: 26 September 2024  |  Reviewed: 23 October 2024  |  Revised: 30 November 2024  |  Accepted: 12 December 2024.